GASTROINTESTINAL STROMAL TUMORS (GIST): DIAGNOSIS AND TREATMENT - N. I. Bogomolov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The article presents the analysis of diagnosis and treatment of 67 patients with gastrointestinal stromal tumors. The mostfrequent location was the stomach, the esophagus took the second place. Among the complications, gastrointestinal bleeding is leading, taking place in half of all cases. The tumor (GIST) develops from the interstitial cells of Cajal and is potentially malignant, the signs of which are established. The incidence of 1 million population is 10-20 cases. The expression of the proto-oncogene c-kit in GIST is detected by an immunohistochemical reaction with the CD117 marker. An erroneous diagnosis in a number of cases was a pseudocyst of the pancreas, found in a CT scan. Tumors bigger than 2 cm in diameter are subject to surgical treatment, smaller ones are recommended for dynamic observation. Organ-preservation operations without lymphodissection are considered acceptable in the course of surgical treatment. Target therapy with tyrosine kinase inhibitors (imatinib, sunitinib, etc.) is used. Two people received chemotherapy in the postoperative period. Histological examination of tumors in most cases detected spindle cell and epithelioid cell variants, in some cases there was a mixed version. GISTs remain the mostfrequent mesenchymal malignant neoplasms of the esophagus, stomach, small intestine, colon and rectum. The article demonstrates variants of GIST in 4 patients with localization of the process in the upper gastrointestinal tract, treatment options, when the final diagnosis was established during surgery with histological and histochemical studies.